Perovskite-based electrocatalysts for oxygen evolution reaction in alkaline media: A mini review - Kim, Dongkyu; Oh, Lee Seul; Park, Jong Hyeok; Kim, Hyung Ju; Lee, Seonggyu; Lim, Eunho (Frontiers in Chemistry, 2022)
Water electrolysis is one of the attractive technologies for producing clean and sustainable hydrogen fuels with high purity. Among the various kinds of water electrolysis systems, anion exchange membrane water electrolysis has received much attention by combining the advantages of alkaline water electrolysis and proton exchange membrane water electrolysis. However, the sluggish kinetics of the oxygen evolution reaction, which is based on multiple and complex reaction mechanisms, is regarded as a major obstacle for the development of high-efficiency water electrolysis. Therefore, the development of high-performance oxygen evolution reaction electrocatalysts is a prerequisite for the commercialization and wide application of water electrolysis systems. This mini review highlights the current progress of representative oxygen evolution reaction electrocatalysts that are based on a perovskite structure in alkaline media. We first summarize the research status of various kinds of perovskite-based oxygen evolution reaction electrocatalysts, reaction mechanisms and activity descriptors. Finally, the challenges facing the development of perovskite-based oxygen evolution reaction electrocatalysts and a perspective on their future are discussed.